Peningkatan Hasil Belajar Matematika dengan Metode Jigsaw Siswa Kelas V SDN Sepakung Kabupaten Semarang - Hartini, Sri (Faculty of Teacher Training and Education of Undaris, 2024)
This research was motivated by the results of fifth grade students' mathematics learning on the volume of space using the lecture and assignment model at SDN Sepakung. The final formulation is whether the jigsaw method can improve the learning outcomes of fifth grade students at SDN Sepakung, Banyubiru subdistrict, Semarang district. This research aims to determine the jigsaw method in improving and improving mathematics learning outcomes for fifth grade students at SDN Sepakung, Banyubiru subdistrict, Semarang Regency. The type of research used is classroom action research. The subjects of this research are class V students at SDN Sepakung, Banyubiru subdistrict, totaling 26 second semester students at state elementary schools. Sepakung, Banyubiru sub-district, Semarang district on April 11 2023. The data collection technique for this research is by assessing the learning outcomes of class V students, observing teacher skills and observing student activities during the learning process. The data analysis used is assessment of class V student learning outcomes, data analysis of teacher skills and student activities. Research results from Pre-Cycle to Cycle II always experience an increase in student learning outcomes. In Cycle I it increased to 15 students who completed their studies with a percentage of 58%. In Cycle II it increased again to 23 students who completed with a percentage of 88% and had met the completeness criteria, namely 75%. Thus, this research is sufficient to reach Cycle II, because the application of the Jigsaw type model can improve student learning outcomes. Improvement of teacher skills in teaching in cycle I was 52.78 converted to a scale of 4 to 2.11 with sufficient qualifications, in cycle II it was 85 converted to a scale of 4 to 3.33 with good qualifications.Keywords: Improvement, Learning Outcomes, Jigsaw Method.